Haldun Taner'in benzetmeci oyunları üzerine göstergebilimsel bir çözümleme - Dicle Başbuğ, Esra. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
In this study, Haldun Taner's five mimetic plays which belong to his first period of theatre carrier are analyzed by means of the semiotic method. As a semiotic analysis requires, in each play meaning levels are determined, functions of narration units that help us find the abstract meaning of the text are considered and in conclusion, the deep structure that all meanings of plays are established on is revealed. At the end of this analysis that performed by semiotic method, it is concluded that in spite of the fact that these plays of Haldun Taner seem to have different features in form and content, at deep structure of all plays there is the same "conflict" between the old/new values which occur after the economical changing period in Turkey around 1950's.
Keywords: Taner, Haldun, 1915-1986 -- Criticism and interpretation.; Theater -- Turkey -- History and criticism -- 20th century.